2010
DOI: 10.1016/j.jvs.2010.04.030
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled trial of endovenous thermal ablation using the 810-nm wavelength laser and the ClosurePLUS radiofrequency ablation methods for superficial venous insufficiency of the great saphenous vein

Abstract: Both methods of endovenous ablation effectively reduce symptoms of superficial venous insufficiency. EVL is associated with greater bruising and discomfort in the perioperative period but may provide a more secure closure over the long-term than RFA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
3
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(65 citation statements)
references
References 17 publications
1
53
3
8
Order By: Relevance
“…All previous studies have reported that the greatest superiority of RF over EVLA is greater patient satisfaction. 12,[17][18][19] In our study, however, patient satisfaction was higher in the EVLA group, while better results for criteria such as intraoperative and postoperative pain, postoperative analgesic requirement, return to activity and return to work were obtained in the EVLA group. Of these, postoperative pain and time to return to activity were statistically significant (P < 0.035 and P < 0.001, respectively).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…All previous studies have reported that the greatest superiority of RF over EVLA is greater patient satisfaction. 12,[17][18][19] In our study, however, patient satisfaction was higher in the EVLA group, while better results for criteria such as intraoperative and postoperative pain, postoperative analgesic requirement, return to activity and return to work were obtained in the EVLA group. Of these, postoperative pain and time to return to activity were statistically significant (P < 0.035 and P < 0.001, respectively).…”
Section: Discussioncontrasting
confidence: 56%
“…Publications generally report that both methods have the same levels of successful ablation, but that pain levels and rates of complications following RFA are lower compared to EVLA. 12,[16][17][18][19][20] However, these studies have generally used low wavelength laser. Several recent studies suggest that better results are achieved with higher laser wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…A series of recently published reviews in peer-reviewed journals have evaluated either individual techniques or a combination of EVLA, RFA and FS. [46][47][48][49][50][51] All reviews have suggested that these treatments may offer viable alternatives to traditional techniques; there is a non-significant difference in favour of surgery in terms of recurrence, but a significant difference in favour of the minimally invasive techniques in terms of technical failure. Serious adverse events were found to be rare.…”
Section: Discussionmentioning
confidence: 99%
“…The authors state that the 'data suggested that the odds ratios for incomplete occlusion did not differ during follow-up'. However, the review (which does include non-randomised comparative studies) by van den Bos et al, 49 which included a meta-regression of treatment success with time, indicates that relative success rates do vary with time from treatment. A further questionable assumption, which is not tested in sensitivity analysis, is that patients with residual varicosities and incomplete occlusion have the same utility value as untreated patients.…”
Section: Assessment Of Cost-effectivenessmentioning
confidence: 99%
“…Kirurgija male safenske vene zaradi zelo spremenljivega vtočišča v globoko veno zahteva predoperativni pregled z ultrazvokom. Odstranjujemo le njen proksimalni in inkompetentni del (66).…”
Section: Kirurško Zdravljenje Varicunclassified